1993
DOI: 10.1128/jcm.31.8.2057-2060.1993
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnosis of scrub typhus by a passive hemagglutination assay using recombinant 56-kilodalton polypeptides

Abstract: The genes encoding the 56-kDa polypeptides were amplified by polymerase chain reaction from the genomic DNAs of three serotypes ofRicketasia tsutsugamushi, Gifliam, Karp, and Boryong. The amplified products were cloned into expression vector pIH821, and the recombinant antigens were expressed in Escherichia conl as fusion proteins with maltose-binding protein. The recombinant 56-kDa polypeptides were purified by affinity chromatography for the sensitization of sheep erythrocytes. The recombinant 56-kDa polypep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 24 publications
(21 reference statements)
0
50
0
Order By: Relevance
“…PHA was performed using a Genedia TsuTsu PHA II test kit (GreenCross SangA, Yongin city, Kyunggi-do, Korea). This kit is currently used to quantitatively and qualitatively analyse antibodies against O. tsutsugamushi in human sera; it employs sheep red blood cells (RBCs) sensitized to recombinant 56-KDa protein from a Boryoung serovariant of O. tsutsugamushi specific for Korea, as well as the Karp and Gilliam serovariants of O. tsutsugamushi [9].…”
Section: Methodsmentioning
confidence: 99%
“…PHA was performed using a Genedia TsuTsu PHA II test kit (GreenCross SangA, Yongin city, Kyunggi-do, Korea). This kit is currently used to quantitatively and qualitatively analyse antibodies against O. tsutsugamushi in human sera; it employs sheep red blood cells (RBCs) sensitized to recombinant 56-KDa protein from a Boryoung serovariant of O. tsutsugamushi specific for Korea, as well as the Karp and Gilliam serovariants of O. tsutsugamushi [9].…”
Section: Methodsmentioning
confidence: 99%
“…56-kDa protein, which was predicted to be hydrophobic and embedded in the membrane and showed no reactivity with human IgG and IgM antibodies (23). Previous reports have shown that 56-kDa protein was always produced in the form of inclusion body in E. coli (15)(16)(17)(18)(19)(20). However, the recombinant protein was highly soluble in our study.…”
Section: Discussionmentioning
confidence: 52%
“…Recent investigations suggested that the major outer membrane 56-kDa protein is a protective antigen that can be produced as a suitable recombinant protein for a diagnostic reagent purpose (15). Kim et al used a recombinant 56-kDa protein from the Boryong strain fused with maltose binding protein as the antigen in ELISA and a passive hemagglutination test for scrub typhus (17,18). Ching and colleagues have developed a rapid immunochromatographic flow test to detect the anti-O.…”
mentioning
confidence: 99%
“…When the mice became sick, their spleens were aseptically removed, minced and inoculated onto a mouse L cell culture. When about 80% of the cells were infected as confirmed by the IFA test, the cells were harvested and the organisms purified by Percoll density-gradient centrifugation as previously described (7,8,12 typhus including acute fever and skin rashes. A PHA test using rickettsial 56 kDa protein antigen was performed as previously described (8) and the patient's antibody titer was 1:640.…”
Section: Methodsmentioning
confidence: 99%
“…In Korea, scrub typhus is one of the main causes of acute febrile illness, especially in rural areas. The disease has usually been diagnosed serologically by IFA or passive hemagglutination assay (PHA) (1,8), and treatment has been by antibiotics. Because high incidence rate of scrub typhus in the fall harvesting season results in a significant loss of the labor force in rural areas, proper prevention of the disease is desirable.…”
mentioning
confidence: 99%